PENGEMBANGAN INSTRUMEN PENILAIAN BERORIENTASI HOTS PADA MATERI PECAHAN DI SEKOLAH DASAR - Inge Dita Pradina; Sukmawarti (STKIP Subang, 2023)
This research aims to find out how to develop a HOTS-oriented assessment instrument on Fraction material in elementary schools and to obtain learning outcomes from students after working on HOTS-oriented practice questions. This research is a type of development research or Research and Development (R&D). The model used in this development is the ADDIE model. The subjects of this research were class IV students at SD Negeri 105299 Marindal, while the object of this research was a HOTS-oriented assessment instrument on pacahan material in elementary schools. The feasibility of the HOTS-oriented assessment instrument that has been developed is obtained from the results of validation sheet analysis by experts in the field. In this research, the product of developing a HOTS-oriented assessment instrument on fraction material in elementary schools was declared suitable for use..